Miguel Torga viajero por España: La mirada portuguesa sobre las ciudades y pueblos españoles - Navas Sánchez-élez, M.ª Victoria (Revista de Filología Románica, 2008)
This paper is the research and analysis of Diário, A Criação do Mundo, Poemas Ibéricos, Bichos, Portugal and Novos Contos da Montanha by Miguel Torga and his view on Spanish towns and cities.